Examination of Legal, Regulatory and Operational Challenges of Book Publishing in Nigeria - Oguntayo , Clement Taiwo; Olubiyi, Ifeoluwa A. (ABUAD Law Journal, 2025)
In Nigeria, there are many challenges which are incapacitating book publishing and these can be grouped into three broad classifications, namely; legal, regulatory and operational challenges. There is no way a critical analysis can be done on the book industry in Nigeria without dissecting the challenges facing the sector. The aim of this paper is to find an ending solution to these issues in order to enhance maximal performance of the sector for national growth. In discussing the legal challenges of book publishing, the Copyright Act of 2022 which is the principal instrument that governs intellectual property rights in Nigeria is the primary source of this paper while references from other works of scholar shall be the secondary source of information. This paper concludes by suggesting that to book publishing contribute to national developments, the legal framework must be reviewed and regulatory institutions must be strengthened to sanitize the industry. Above all, operational challenges are curbed in order to open the floodgate of solutions to the numerous shortcomings in the industry which have hitherto prevented the sector from making significant impact on the nation’s economy.